On the role and design of dispute settlement procedures in international trade agreements - Maggi, Giovanni 1964-; Staiger, Robert W. (National Bureau of Economic Research, 2008)
"Formal economic analysis of trade agreements typically treats disputes as synonymous with concerns about enforcement. But in reality, most WTO disputes involve disagreements of interpretation concerning the agreement, or instances where the agreement is simply silent. And some have suggested that the WTO's Dispute Settlement Body (DSB) might serve a useful purpose by granting "exceptions" to rigid contractual obligations in some circumstances. In each of these three cases, the role played by the DSB amounts to "completing" various dimensions of an incomplete contract. Moreover, there is a debate among legal scholars on whether or not precedent-setting in DSB rulings may enhance the performance of the institution. All of this points to the importance of understanding the implications of the different possible degrees of activism in the role played by the DSB. In this paper we bring formal analysis to bear on this broad question. We characterize the choice of contractual form and DSB role that is optimal for governments under various contracting conditions. A novel feature of our approach is that it highlights the interaction between the design of the contract and the design of the dispute settlement procedure, and it views these as two components of a single over-arching institutional design problem"--National Bureau of Economic Research web site